Does urinary urgency drive urinary frequency in overactive bladder?. Issue 4 (28th February 2022) - Versi, Eboo; Rovner, Eric S.; Dmochowski, Roger R.; Tu, Le Mai; De Wachter, Stefan
Abstract: Objectives: To determine if reduction in urgency in patients with refractory overactive bladder syndrome (rOAB) is correlated with a reduction in voiding frequency and symptom bother. Methods: Data from a prospective series of women with rOAB undergoing radiofrequency ablation of the subtrigonal tissue, termed selective bladder denervation (SBD), was analyzed. Main outcome measures included urgency voids, nonurgency voids, and urgency urinary incontinence (UUI) epidsodes from a 3‐day voiding diary and quality of life (QoL) measures (Overactive Bladder Questionnaire Short Form [OAB‐q SF]). Results: The dataset comprised 62 completer subjects at 6 months. Compared to baseline, UUI and urgency voids were lower ( P < .001), but nonurgency voids were increased ( P < .001) and QoL measures were improved ( P < .001), but functional bladder capacity did not increase. At baseline and 6 months post treatment, symptom bother was correlated with urgency voids ( P < .05) but inversely correlated with nonurgency voids ( P < .001). Urgency and nonurgency voids were inversely related at baseline and at 6 months ( P < .0001). Following treatment, urgency voids decreased by 41% and nonurgency voids increased by 33%. Conclusions: As with other interventions for OAB, SBD resulted in a reduction in OAB symptoms and an improvement in QoL measures. However, the decrease in urgency voids was offset by an increase in nonurgency voids, suggesting that habit or defensive voiding is a significant driver of urinary frequency. It is not certain if this is a unique finding of the SBD effect, but these data do suggest that analyses of outcomes of other OAB interventions are warranted to gain a better understanding of the genesis of OAB symptoms.